Effect of implementation of a 12-dose once-weekly treatment (3HP) in addition to standard regimens to prevent TB on completion rates: Interrupted time series design. (April 2022) - Alvarez, Gonzalo G.; Sullivan, Kathryn; Pease, Christopher; Van Dyk, Deborah; Mallick, Ranjeeta; Taljaard, Monica; Grimshaw, Jeremy M.; Amaratunga, Kanchana; Allen, Crystal; Brethour, Kaitlyn; Mulpuru, Sunita; Pakhale, Smita; et al.
Highlights: 3HP to treat LTBI is an alternative for TPT regular regimens 3HP significantly increases the proportion of patients completing TPT treatment The use of 3HP in Canada should be accelerated Abstract: Objectives: We aimed to determine if offering a 12-dose once-weekly treatment (3HP) as an additional treatment option would result in an increase in the overall proportion of patients completing TB preventive treatment (TPT) above the baseline rate. Methods: We analyzed outcomes in consecutive adults referred to a TB clinic from January 2010 to May 2019. Starting December 2016, 3HP was offered as an alternative to standard clinic regimens which included 9 months of daily isoniazid or 4 months of daily rifampin. The primary outcome was the proportion of patients who completed TPT among all patients who started treatment. Using segmented autoregression analysis, we compared completion at the end of the study with projected completion had the intervention not been introduced. Results: A total of 2803 adults were referred for assessment over the study period. There was an absolute increase in completions among those who started a treatment of 19.0% at the end of the study between the observed intervention completion rate and the projected completion rate from the baseline study period (the completion rate had the 3HP intervention not been introduced) (76% observed vs 57% projected; 95% CI 6.6 to 31.4%; p = 0.004) and an absolute increase among those who were offered treatment (17.3%; 95% CI, 2.3 to 32.3%; p = 0.025). Conclusions: The introduction of 3HP for TPT as an alternative to the regular regimens offered resulted in a significant increase in the proportion of patients completing treatment. Our study provides evidence to support accelerated use of 3HP in Canada.